Outcome of Hepatitis E Virus Infection in Patients With Inflammatory Arthritides Treated With Immunosuppressants. Issue 14 (April 2015) - Bauer, Hélène; Luxembourger, Cécile; Gottenberg, Jacques-Eric; Fournier, Sophie; Abravanel, Florence; Cantagrel, Alain; Chatelus, Emmanuel; Claudepierre, Pascal; Hudry, Christophe; Izopet, Jacques; Fabre, Sylvie; Lefevre, Guillaume; et al.
<x xml:space="preserve">Abstract</x> Abstract The clinical presentation and outcome of hepatitis E virus (HEV) infection in inflammatory rheumatic diseases are unknown. We aimed to investigate the severity of acute HEV infection and the risk of chronic viral replication in patients with inflammatory arthritides treated with immunosuppressive drugs. All rheumatology and internal medicine practitioners belonging to the Club Rhumatismes et Inflammation in France were sent newsletters asking for reports of HEV infection and inflammatory arthritides. Baseline characteristics of patients and the course of HEV infection were retrospectively assessed by use of a standardized questionnaire. From January 2010 to August 2013, we obtained reports of 23 cases of HEV infection in patients with rheumatoid arthritis (n = 11), axial spondyloarthritis (n = 5), psoriatic arthritis (n = 4), other types of arthritides (n = 3). Patients received methotrexate (n = 16), antitumor necrosis factor α agents (n = 10), rituximab (n = 4), abatacept (n = 2), tocilizumab (n = 2), and corticosteroids (n = 10, median dose 6 mg/d, range 2–20). All had acute hepatitis: median aspartate and alanine aminotransferase levels were 679 and 1300 U/L, respectively. Eleven patients were asymptomatic, 4 had jaundice. The HEV infection diagnosis relied on positive PCR results for HEV RNA (n = 14 patients) or anti-HEV IgM positivity (n = 9). Median follow-up was 29 months (range 3–55). Treatment included discontinuation of immunosuppressants for 20 patients and ribavirin treatment for 5. Liver enzyme levels normalized and immunosuppressant therapy could be reinitiated in all patients. No chronic infection was observed. Acute HEV infection should be considered in patients with inflammatory rheumatism and elevated liver enzyme values. The outcome of HEV infection seems favorable, with no evolution to chronic hepatitis or fulminant liver failure.